2016
DOI: 10.1007/s00264-016-3150-2
|View full text |Cite
|
Sign up to set email alerts
|

Conversion from knee arthrodesis to arthroplasty: systematic review

Abstract: Purpose Arthrodesis (AD) of the knee reduces pain and provides stability, but has severe functional and social limitations. There has been ample discussion on the value of a conversion of an AD to a total knee arthroplasty (TKA). The aim of this study was to perform a review and meta-analysis of the current literature on conversion of an AD to TKA and assess clinical outcome, complication rate, surgical technique and overall patient-related outcome measures. Methods PubMed, Embase, Web of Science, Cochrane, CE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 21 publications
0
8
1
Order By: Relevance
“…Nevertheless, most patients were satisfied with the procedure. Kernkamp et al [11] reported in their analysis of 123 converted TKA a mean gain of flexion to be 80 and an improvement of Hospital for Special Surgery score by 20 points. However, they reported complications including skin necrosis (25%), infection (11%), revision (11%), and refusion of the knee (4.9%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, most patients were satisfied with the procedure. Kernkamp et al [11] reported in their analysis of 123 converted TKA a mean gain of flexion to be 80 and an improvement of Hospital for Special Surgery score by 20 points. However, they reported complications including skin necrosis (25%), infection (11%), revision (11%), and refusion of the knee (4.9%).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, realistic patient expectations with regard to the functional outcome along with the willingness and motivation to continuously participate in the postoperative follow-up care are needed for the success of the procedure [1,9,10]. A recent meta-analysis showed good clinical results but a high complication rate of up to 65% [11]. The importance of a thorough patient selection process is emphasized and aids in the outcome of this rare procedure.…”
Section: Introductionmentioning
confidence: 99%
“…During exposure, stiff knees may need a rectus snip for exposure. Knees with osseous ankylosis in extension almost always need VY quadricepsplasty before the patella can be everted to minimize the risk of patellar tendon avulsion 11 . Aglietti and Buzzi recommended early quadricepsplasty to aid in exposure and patellar eversion without compromising the integrity of the patellar tendon 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Most are young or middle-aged, and arthrodesis can be used as a transitional operation to control inflammation. After inflammation is controlled, a second-stage knee replacement can be selected to restore joint function, whereas the first-stage knee arthroplasty has a higher cost and is accompanied by a higher risk of TB recurrence [23,24]. In addition, for people with economic difficulties, especially for older patients, arthrodesis can also be used as the final treatment to relieve pain and improve quality of life.…”
Section: Discussionmentioning
confidence: 99%